Pengaruh Pemberian Pakan Ekstrak Buah Kiwi (Actinidia deliciosa (A. Chev.) C.F. Liang & A.R. Ferguson) terhadap Sintasan dan Morfologi Organ Reproduksi Lalat Buah (Drosophila melanogaster Meigen, 1830) Iradiasi Sinar Ultraviolet - Nafisa Kusumawati; Ignatius Sudaryadi (Berkala Ilmiah Biologi, 2022)
UV (ultraviolet) radiation is one of the radiations that are naturally emitted by the sun. As the result of climate changes, the earth's ozone layer changes and the UV light radiation to the earth's surface increases. The negative effect of UV radiation is increase due to the production of ROS (Reactive Oxygen Species) or free radicals in the body. UV radiation protection can be done by increasing the intake of antioxidant-rich foods as free radical inhibitors. Actinidia deliciosa or kiwifruit is a antioxidants-rich fruit including vitamin C. This research was carried out with Drosophila melanogaster as a animal model because it is easy to breed in the laboratory, has a short life cycle, and produces large numbers of eggs. Drosophila melanogaster or fruit flies are the most commonly used of animal models in the biomedical and pharmacological fields. This study aims to determine the effect of UV radiation on fruit fly survival at the larval, pupa, and imago stages and the morphology changes of male and female reproductive organs, as well as to determine the effect of feeding kiwi fruit extract on survival rate and morphology changes of male and female reproductive organs of UV irradiated fruit fly. This research was conducted by providing UV exposure treatment and without UV radiation treatment to fruit flies for 2 hours on banana and kiwi feed medium. Data analysis was carried out with the One Way Anova test followed by the Duncan test. The results showed that UV radiation could affect the survival and morphology of the reproductive organs of fruit flies. The survival rate in the control treatment was 58%, PK treatment 81%, PPUV treatment 45%, and PKUV treatment 47%.